Violence Against Women and Its Consequences on Women’s Reproductive Health and Depression: A Jordanian Sample - Damra, Jalal K. (Journal of interpersonal violence, 2021)
The aims of this study were to investigate the women’s current reproductive health (RH) status, depression levels, and to clarify the relationships between the violence against women and depression and the RH components. Three hundred women participated in the study. Data were collected from the Women Health Center (WHC) in Prince Faisal hospital in Rusaifa, Jordan. The findings revealed that around 25.9%, 13.1%, 83.2%, and 65.1% of the participant women had been exposed to physical, sexual, control, and psychological violence, respectively. Around 77.7% of women were using contraceptives; oral contraceptives and intrauterine devices (IUDs) were the most common family planning methods used. In addition, the results revealed that 50% of women were suffering from significant levels of depression. A positive relationship between exposure to all violence types and women’s depression levels was found but not for all RH components.